Numerical Validation of Differential Settlement in the Transition Zone of Embankment-Slab on Pile Over Soft Soils - Hanifan Ihsani; Trihanyndio Rendy Satrya; Ria Asih Aryani Soemitro (International Journal Labs, 2025)
Differential settlement in the transition zone between embankment segments and rigid structures such as Slab-on-Pile is one of the most critical issues in toll road construction on soft soil, as it may reduce ride comfort, safety, and service life. In the Serang–Panimbang Toll Road Section III Project, the applied ground treatment method consists of Free Draining Granular Material (FDGM) supporting the approach embankment and bored piles as the abutment foundation for the Slab-on-Pile system. This study aims to evaluate the performance of the existing treatment method by comparing settlement predictions derived from one-dimensional analytical methods (Terzaghi’s theory for embankments and the Boussinesq and Poulos–Davis methods for abutments) with two-dimensional numerical modeling using PLAXIS. The resulting settlement profile in the transition zone is then analyzed to assess the potential for differential settlement with respect to the applicable serviceability limits. The validation results show a strong agreement between analytical and numerical methods, with settlement deviations of 6.09% for the embankment and 4.93% for the abutment. Nevertheless, the embankment over FDGM experiences a total settlement of 51.90 cm, while the Slab-on-Pile abutment settles only 6.10 cm, producing a differential settlement of 45.80 cm, far exceeding the allowable limit. These findings indicate that the use of FDGM alone is insufficient to accommodate the high compressibility of the thick soft soil deposit at the study location.